2003
DOI: 10.1016/s0149-2918(03)80068-1
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, clinical trial of the effects of pioglitazone on glycemic control and dyslipidemia in oral antihyperglycemic medication-naive patients with type 2 diabetes mellitus

Abstract: Objective: The goal of this study was to compare the effects of 2 doses of pioglitazone hydrochloride (a thiazolidinedione insulin sensitizer) with placebo on glycated hemoglobin (HbAlc), insulin sensitivity, and lipid profiles in patients with type 2 diabetes mellitus who had suboptimal glycemic control and mild dyslipidemia. Methods:Patients with type 2 diabetes mellitus (HbAlc >6.5% and <9.8%) who had not previously received insulin or oral antihyperglycemic medications (OAMs) were randomized to treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
77
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 34 publications
10
77
1
2
Order By: Relevance
“…In addition, PIO-based regimens significantly reduced fasting serum insulin levels, C-peptide levels, and 32-33 split pro-insulin levels over the 52-week time course, while GLIC-based regimens were associated with net increases in each of these measures [5]. These data are consistent with previous studies investigating the effects of PIO monotherapy on insulin sensitivity [19,20], and highlight an important difference between the mechanisms of action of PIO (increasing insulin sensitivity) and GLIC (increasing insulin secretion). This distinction may be important in the long-term care of patients with type 2 diabetes given the association of insulin resistance with the development of cardiovascular complications in this population [8][9][10][11].…”
Section: Resultssupporting
confidence: 89%
“…In addition, PIO-based regimens significantly reduced fasting serum insulin levels, C-peptide levels, and 32-33 split pro-insulin levels over the 52-week time course, while GLIC-based regimens were associated with net increases in each of these measures [5]. These data are consistent with previous studies investigating the effects of PIO monotherapy on insulin sensitivity [19,20], and highlight an important difference between the mechanisms of action of PIO (increasing insulin sensitivity) and GLIC (increasing insulin secretion). This distinction may be important in the long-term care of patients with type 2 diabetes given the association of insulin resistance with the development of cardiovascular complications in this population [8][9][10][11].…”
Section: Resultssupporting
confidence: 89%
“…These studies have also reported that pioglitazone modulates carbohydrate and lipid metabolism, increases insulin sensitivity, affects vasculature and may improve some of the risk factors associated with the metabolic syndrome [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…Several clinical trials have demonstrated the short-term beneficial effects of pioglitazone on glycaemic control, both alone [6][7][8][9][10][11] and when added as a second agent in combination therapy [12][13][14][15]. These studies have also reported that pioglitazone modulates carbohydrate and lipid metabolism, increases insulin sensitivity, affects vasculature and may improve some of the risk factors associated with the metabolic syndrome [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Edema has been reported in up to 16% of patients treated with thiazolidinedione monotherapy (9,12,(15)(16)(17)(18). Both muraglitazar and pioglitazone therapy were associated with edema (11.8 and 8.9%, respectively, at week 50) in the present study.…”
Section: Safetymentioning
confidence: 99%